Microorganismos celulolíticos para la descomposición de la cáscara del coco en el sitio “Sosote”, cantón Rocafuerte - Macías Alcívar, Jorge Omar (2023)
The objective of the present investigation was to establish a degradation system with cellulolytic microorganisms for the use of coconut residues from the "Sosote" site, Rocafuerte canton, for which a socio-environmental diagnosis of the coconut production sector was carried out, experiments were proposed. with cellulolytic microorganisms and the percentage of degradability was determined. The research was experimental developed in two phases, one in the laboratory and one in the field. As results, the determination of the coconut production line in Sosote shows that 100% of the producers are men with an age range of between 30 and 50 years, dedicating themselves to coconut production for 10 years; 80% produce between 5,000 and 10,000 coconuts per month, with production areas ranging from 2 to 6 hectares, with approximately 2,000 plants/Ha. The growth of Bacillus and Trichoderma microorganisms was positive in the prepared culture media, for this reason they were used to add to the composting piles to which pH (7.35 to 7.62), temperature (30-32ºC) were monitored. ), electrical conductivity (131.37-148.23 µS/cm) and humidity (35 to 39%); the best C/N ratio was for T1 (29.17%) and T2 (26.92%), Stack 1 (ground/trimmed coconut shell + chicken manure + 400 mL of diluted microorganisms) presented the best average in the root growth with a value of 8.39 cm and it was also the best treatment used with 91.77% in the germination index.